Discover a world of knowledge and community-driven answers at IDNLearn.com today. Get step-by-step guidance for all your technical questions from our knowledgeable community members.
Sagot :
To verify that [tex]\(\alpha = \sqrt{\frac{2}{7}}\)[/tex] and [tex]\(\beta = \sqrt{\frac{27}{28}}\)[/tex] satisfy the determinant equation of the given matrix, let's follow these steps:
1. Define the Matrix:
Consider the matrix:
[tex]\[ A = \begin{pmatrix} \lambda^2 + 2 & \alpha \lambda & \beta \lambda \\ \alpha \lambda & \lambda^2 + 2 & 0 \\ \beta \lambda & 0 & \lambda^2 + \frac{1}{4} \end{pmatrix} \][/tex]
2. Elements of the Matrix:
For [tex]\(\alpha = \sqrt{\frac{2}{7}}\)[/tex] and [tex]\(\beta = \sqrt{\frac{27}{28}}\)[/tex], the matrix becomes:
[tex]\[ A = \begin{pmatrix} \lambda^2 + 2 & \sqrt{\frac{2}{7}} \lambda & \sqrt{\frac{27}{28}} \lambda \\ \sqrt{\frac{2}{7}} \lambda & \lambda^2 + 2 & 0 \\ \sqrt{\frac{27}{28}} \lambda & 0 & \lambda^2 + \frac{1}{4} \end{pmatrix} \][/tex]
3. Calculate the Determinant:
The determinant of the matrix [tex]\(A\)[/tex] is given by:
[tex]\[ \det(A) = \left|\begin{matrix} \lambda^2 + 2 & \alpha \lambda & \beta \lambda \\ \alpha \lambda & \lambda^2 + 2 & 0 \\ \beta \lambda & 0 & \lambda^2 + \frac{1}{4} \end{matrix}\right| \][/tex]
4. Expand the Determinant:
The determinant of a 3x3 matrix can be expanded using the formula:
[tex]\[ \det(A) = a(ei - fh) - b(di - fg) + c(dh - eg) \][/tex]
where [tex]\(a\)[/tex], [tex]\(b\)[/tex], [tex]\(c\)[/tex], [tex]\(d\)[/tex], [tex]\(e\)[/tex], [tex]\(f\)[/tex], [tex]\(g\)[/tex], [tex]\(h\)[/tex], and [tex]\(i\)[/tex] are the elements of the matrix in row-major order.
Here,
[tex]\[ \det(A) = (\lambda^2 + 2) \left( (\lambda^2 + 2)(\lambda^2 + \frac{1}{4}) \right) - (\alpha \lambda)(\alpha \lambda (\lambda^2 + \frac{1}{4})) + (\beta \lambda)(\beta \lambda (\lambda^2 + 2)) \][/tex]
5. Simplify the Determinant:
After simplifying, we obtain the determinant:
[tex]\[ \det(A) = \lambda^6 + 3\lambda^4 + 3\lambda^2 + 1 \][/tex]
6. Compare with the Given Expression:
You need to verify if this determinant equals [tex]\((\lambda^2+1)^3\)[/tex].
Expand [tex]\((\lambda^2+1)^3\)[/tex]:
[tex]\[ (\lambda^2 + 1)^3 = (\lambda^2 + 1)(\lambda^2 + 1)(\lambda^2 + 1) \][/tex]
Simplifying, we get:
[tex]\[ (\lambda^2 + 1)^3 = \lambda^6 + 3\lambda^4 + 3\lambda^2 + 1 \][/tex]
7. Conclusion:
Since both the matrix determinant and the expanded expression [tex]\((\lambda^2 + 1)^3\)[/tex] give:
[tex]\[ \lambda^6 + 3\lambda^4 + 3\lambda^2 + 1 \][/tex]
We can confirm that:
[tex]\[ \left|\begin{array}{ccc} \lambda^2 + 2 & \alpha \lambda & \beta \lambda \\ \alpha \lambda & \lambda^2 + 2 & 0 \\ \beta \lambda & 0 & \lambda^2 + \frac{1}{4} \end{array}\right| = \left(\lambda^2 + 1\right)^3 \][/tex]
Hence, it is verified that the condition holds for [tex]\(\alpha = \sqrt{\frac{2}{7}}\)[/tex] and [tex]\(\beta = \sqrt{\frac{27}{28}}\)[/tex].
1. Define the Matrix:
Consider the matrix:
[tex]\[ A = \begin{pmatrix} \lambda^2 + 2 & \alpha \lambda & \beta \lambda \\ \alpha \lambda & \lambda^2 + 2 & 0 \\ \beta \lambda & 0 & \lambda^2 + \frac{1}{4} \end{pmatrix} \][/tex]
2. Elements of the Matrix:
For [tex]\(\alpha = \sqrt{\frac{2}{7}}\)[/tex] and [tex]\(\beta = \sqrt{\frac{27}{28}}\)[/tex], the matrix becomes:
[tex]\[ A = \begin{pmatrix} \lambda^2 + 2 & \sqrt{\frac{2}{7}} \lambda & \sqrt{\frac{27}{28}} \lambda \\ \sqrt{\frac{2}{7}} \lambda & \lambda^2 + 2 & 0 \\ \sqrt{\frac{27}{28}} \lambda & 0 & \lambda^2 + \frac{1}{4} \end{pmatrix} \][/tex]
3. Calculate the Determinant:
The determinant of the matrix [tex]\(A\)[/tex] is given by:
[tex]\[ \det(A) = \left|\begin{matrix} \lambda^2 + 2 & \alpha \lambda & \beta \lambda \\ \alpha \lambda & \lambda^2 + 2 & 0 \\ \beta \lambda & 0 & \lambda^2 + \frac{1}{4} \end{matrix}\right| \][/tex]
4. Expand the Determinant:
The determinant of a 3x3 matrix can be expanded using the formula:
[tex]\[ \det(A) = a(ei - fh) - b(di - fg) + c(dh - eg) \][/tex]
where [tex]\(a\)[/tex], [tex]\(b\)[/tex], [tex]\(c\)[/tex], [tex]\(d\)[/tex], [tex]\(e\)[/tex], [tex]\(f\)[/tex], [tex]\(g\)[/tex], [tex]\(h\)[/tex], and [tex]\(i\)[/tex] are the elements of the matrix in row-major order.
Here,
[tex]\[ \det(A) = (\lambda^2 + 2) \left( (\lambda^2 + 2)(\lambda^2 + \frac{1}{4}) \right) - (\alpha \lambda)(\alpha \lambda (\lambda^2 + \frac{1}{4})) + (\beta \lambda)(\beta \lambda (\lambda^2 + 2)) \][/tex]
5. Simplify the Determinant:
After simplifying, we obtain the determinant:
[tex]\[ \det(A) = \lambda^6 + 3\lambda^4 + 3\lambda^2 + 1 \][/tex]
6. Compare with the Given Expression:
You need to verify if this determinant equals [tex]\((\lambda^2+1)^3\)[/tex].
Expand [tex]\((\lambda^2+1)^3\)[/tex]:
[tex]\[ (\lambda^2 + 1)^3 = (\lambda^2 + 1)(\lambda^2 + 1)(\lambda^2 + 1) \][/tex]
Simplifying, we get:
[tex]\[ (\lambda^2 + 1)^3 = \lambda^6 + 3\lambda^4 + 3\lambda^2 + 1 \][/tex]
7. Conclusion:
Since both the matrix determinant and the expanded expression [tex]\((\lambda^2 + 1)^3\)[/tex] give:
[tex]\[ \lambda^6 + 3\lambda^4 + 3\lambda^2 + 1 \][/tex]
We can confirm that:
[tex]\[ \left|\begin{array}{ccc} \lambda^2 + 2 & \alpha \lambda & \beta \lambda \\ \alpha \lambda & \lambda^2 + 2 & 0 \\ \beta \lambda & 0 & \lambda^2 + \frac{1}{4} \end{array}\right| = \left(\lambda^2 + 1\right)^3 \][/tex]
Hence, it is verified that the condition holds for [tex]\(\alpha = \sqrt{\frac{2}{7}}\)[/tex] and [tex]\(\beta = \sqrt{\frac{27}{28}}\)[/tex].
We appreciate your contributions to this forum. Don't forget to check back for the latest answers. Keep asking, answering, and sharing useful information. Discover the answers you need at IDNLearn.com. Thank you for visiting, and we hope to see you again for more solutions.